2021
DOI: 10.1007/s11357-021-00409-y
|View full text |Cite
|
Sign up to set email alerts
|

The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification

Abstract: Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…However, Stefanini et al found out that 39% of COVID-19 patients with STEMI had negative invasive coronary angiography (ICA) probably for the higher prevalence of type-2 MI in patients during the acute phase of COVID-19. These data further supported the use of CCTA in COVID-19 patients [47], also having the advantage to simultaneously rule-out coronary artery disease (CAD) and pulmonary embolism (PE) using a triple rule-out scanning protocol [23,24] and to refine risk stratification of COVID-19 patients with the quantification of coronary artery calcium score (CAC) [7,9,10,16,25,48].…”
Section: Cardiac Imaging In Covid-19mentioning
confidence: 69%
See 2 more Smart Citations
“…However, Stefanini et al found out that 39% of COVID-19 patients with STEMI had negative invasive coronary angiography (ICA) probably for the higher prevalence of type-2 MI in patients during the acute phase of COVID-19. These data further supported the use of CCTA in COVID-19 patients [47], also having the advantage to simultaneously rule-out coronary artery disease (CAD) and pulmonary embolism (PE) using a triple rule-out scanning protocol [23,24] and to refine risk stratification of COVID-19 patients with the quantification of coronary artery calcium score (CAC) [7,9,10,16,25,48].…”
Section: Cardiac Imaging In Covid-19mentioning
confidence: 69%
“…Coronary artery calcium score (CAC) is an established biomarker for risk stratification in patients with suspected CAD and its value has been also documented in COVID-19 setting [25]. Several studies [9,10,16,25] showed that elevated CAC score, specially >400 AU, is associated to poor prognosis. Female patients showed lower mortality compared to men.…”
Section: Acute Cardiovascular Damage: the Role Of Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relatively low prevalence of prior revascularization among patients with COVID-19, this event significantly increases the risk of short-term mortality, with odds ratios ranging from 1.8 to 12.8 [38]. This statement is supported by the results of several foreign studies, which demonstrated that clinical outcomes in patients with COVID-19 are closely related to comorbidities in patients [39]. Identification of risk factors associated with poor outcomes in patients with COVID-19 remains critical to identifying vulnerable populations [40].…”
Section: Prognostic Risks About the Course Of Coronary Artery Disease...mentioning
confidence: 86%
“…Most likely, several sex-related factors contribute to the higher risk of males for poorer COVID-19 outcomes. A study of 1,683 Italian patients who underwent chest computed tomography at admission showed that men had a higher prevalence of cardiovascular comorbidities, more coronary calci cations, and a higher coronary calcium score than females [22]. Notably, the higher coronary calci c burden of men appeared to be associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%